Tax Avoidance Analysis With Thin Capitalisation - Andre Suryaningprang; Andhika Mochamad Siddiq; Dewi Yuliati Indah; Wentri Merdiani (Budapest International Research and Critics University, 2022)
This study aims to analyze thin capitalization which is used as a way of tax avoidance. This study uses independent variables, namely multinational, managerial ownership, audit committee, while the control variables are effective tax rates, profit growth, return on assets, firm size, current ratio, capital intensity, and inventory intensity. The population of this study consisted of all non-financial companies listed on the Indonesia Stock Exchange from 2015-2019. The sample of this research is multinational non-financial companies which means having subsidiaries outside Indonesia. The statistical method used in this research is multiple linear regression analysis. The results of this study indicate that multinationality, managerial ownership, and audit committee have no significant effect on thin capitalization. As for the control variables, return on assets and firm size have a significant effect on thin capitalization.